2021
DOI: 10.3390/su13116392
|View full text |Cite
|
Sign up to set email alerts
|

Specified Dosages of Biochar Application Not Impact Native Organic Carbon but Promote a Positive Effect on Native Humic Acid in Humicryepts Soil

Abstract: Biochar is considered to have potential use in carbon (C) sequestration and has been widely used in soil amendment. Humic substances (HSs), assigned as the stable organic C, have obvious agronomic benefits. However, the response mechanisms of these carbonaceous substances to biochar are unclear in biochar-amended soils. In a two-year experiment, the δ13C technique was employed to trace the fate of the biochar-derived C in HSs and evaluate the effects of four treatments, including no biochar control (CK) and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…The increase in TC values between 12 and 24th week of experiment was 10%, suggesting carbon sequestration ability of applied amendments. Similar ability of biochar (24 t ha −1 ) to improve SOC stocks and improve C stability was reported by Li et al [42].…”
supporting
confidence: 84%
“…The increase in TC values between 12 and 24th week of experiment was 10%, suggesting carbon sequestration ability of applied amendments. Similar ability of biochar (24 t ha −1 ) to improve SOC stocks and improve C stability was reported by Li et al [42].…”
supporting
confidence: 84%
“…Numerous studies on the effects of straw biochar incorporation into soils have revealed soil quality improvement, a reduction in greenhouse gas emissions and plant growth promotion [3][4][5][6]. For CO 2 sequestration, it is generally accepted that biochar application is beneficial to the C sink in most categories of soil [7,8]. Owing to its chemical and biological inertness, as well as the physical protection of its surrounding environment, straw biochar trapped 47% of soil organic carbon (SOC) in rice cultivation soil and 57% in maize cultivation soil [9].…”
Section: Introductionmentioning
confidence: 99%